Improving Employee Quality to Support Operations at Hotel Amarelo Solo - Ariyadi; Wijoyo, Tuwuh Adhistyo (International Journal of Integrative Sciences, 2024)
This research aims to identify strategies for improving employee capacity to support operational excellence at Hotel Amarelo Solo. The study highlights challenges such as limited employee skills, lack of structured training programs, and high turnover rates, which negatively impact service quality and guest satisfaction. A qualitative approach was adopted, utilizing a literature review to analyze data from relevant journals and research documents. The study employs thematic and narrative analyses to explore factors influencing employee capacity and provide actionable recommendations. The findings indicate that capacity development plays a vital role in enhancing organizational performance, particularly in the hospitality industry. Needs-based and innovative training programs, supported by technological integration, significantly improve employee skills, motivation, and service quality. Additionally, fostering a supportive and harmonious work environment enhances employee well-being and loyalty, further reducing turnover rates. The study concludes that structured capacity development, aligned with operational needs and long-term organizational goals, is essential for sustaining competitiveness in the hospitality sector